2019
DOI: 10.1038/s41374-018-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 1 and survivin as potential therapeutic targets against nasal natural killer/T-cell lymphoma

Abstract: Nasal natural killer/T-cell lymphoma (NNKTL) is closely associated with Epstein-Barr virus (EBV) and is characterized by poor prognosis, resulting from rapid progression of lesions in the affected organs. Recent data have shown that NNKTL is associated with the aberrant expression of cyclin-dependent kinase 1 (CDK1) and its downstream target survivin, but little is known about the functional roles of CDK1 and survivin in NNKTL. In the current study, we show that knockdown of the EBV-encoded oncoprotein latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…One of the latest research reported that upregulation of CDK1 was essential for nasal natural killer/T-cell lymphoma progression and targeting CDK1 might benefit the treatment of NNKTL. [ 58 ] Similar results were reported in cervical cancer by Li. [ 59 ] In bladder cancer, it is demonstrated that Glaucocalyxin A regulated the expression of CDK1 to induces G2/M cell cycle arrest and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…One of the latest research reported that upregulation of CDK1 was essential for nasal natural killer/T-cell lymphoma progression and targeting CDK1 might benefit the treatment of NNKTL. [ 58 ] Similar results were reported in cervical cancer by Li. [ 59 ] In bladder cancer, it is demonstrated that Glaucocalyxin A regulated the expression of CDK1 to induces G2/M cell cycle arrest and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, LMP1 acts as an oncoprotein because it can induce the transformation of rodent fibroblast cell lines [ 103 ]. According to our previous findings, as described above [ 85 , 86 , 87 , 88 , 90 , 94 ], LMP1 is thought to have a pivotal role in the lymphomagenesis of ENKTL-NT as well. At the point of regulation of LMP1 expression, EBNA-2 enhanced the expression by activating the LMP1 promotor in the type III latency cells, such as EBV immortalized B-lymphocytes [ 104 ]; however, the regulation system had unclear type II latency cell levels, which did not express EBNA-2.…”
Section: Environmental Factors Affecting Ebv Statusmentioning
confidence: 80%
“…On the other hand, interferon-gamma-inducible protein-10 (IP-10) served as an autocrine invasion factor [ 86 ]. Cyclin-dependent kinase (CDK)1 and survivin were highly expressed in the cells and transmitted cell proliferation signals [ 90 ]. Conversely, micro RNA (miR)-15a was less expressed in the cells, and reduced antiproliferative signals [ 87 ].…”
Section: Proliferation and Invasion Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LMP1/2a-specific cytotoxic T-cells have been shown to act as novel adoptive immunotherapies with successful outcomes in overall survival (100%) and progression-free survival (90%) in a study of 10 ENKTL patients who showed complete response to induction therapy [50]. Though clinical trials have not yet been established, inhibition of survivin by pharmaceuticals such as terameprocol have been shown to increase apoptosis and decrease tumor cell proliferation [15,51]. In a study by Go et al, dozens of miRNAs were shown to be down-regulated by methylation, and key miRNAs, including miR-34a and miR-181c were identified as potential therapeutic targets given their role in regulating PDGFRα, STAT3, and K-RAS [52].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%